2017
DOI: 10.1002/anie.201609708
|View full text |Cite
|
Sign up to set email alerts
|

GXXXG‐Mediated Parallel and Antiparallel Dimerization of Transmembrane Helices and Its Inhibition by Cholesterol: Single‐Pair FRET and 2D IR Studies

Abstract: Small-residue-mediated interhelical packings are ubiquitously found in helical membrane proteins, although their interaction dynamics and lipid dependence remain mostly uncharacterized. We used a single-pair FRET technique to examine the effect of a GXXXG motif on the association of de-novo designed (AALALAA)3 helices in liposomes. Dimerization occurred with sub-second lifetimes, which was abolished by cholesterol. Utilizing the nearly instantaneous time-resolution of 2D IR spectroscopy, parallel and antiparal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
(47 reference statements)
0
26
0
Order By: Relevance
“…There are a number of GXXXG motifs in the protein sequence of HSPG ( Fig. 15B), suggesting that this protein could form a dimer [28].…”
Section: Co-purification Of Hspgmentioning
confidence: 99%
“…There are a number of GXXXG motifs in the protein sequence of HSPG ( Fig. 15B), suggesting that this protein could form a dimer [28].…”
Section: Co-purification Of Hspgmentioning
confidence: 99%
“…Virus infection smFRET imaging assay revealed structure arrangement of critical binding domains between the membrane receptor and virus spike [124,129] Protein aggregation Intramolecular FRET showed the states of aggregation in various conditions quantitatively [141][142][143][144][145] Intermolecular FRET exhibited the aggregating principle [144,145] Protein-Lipid Cross-membrane transport smFRET with long critical transfer distance detected both parallel and antiparallel dimers of transmembrane helix regulated by cholesterol [132,133] Protein-Nucleic acid DNA synthesis Drops in FRET efficiency indicated DNA synthesis with label on polymerase or on template [146,147] Various labeling strategies can present the states of different active domains on polymerase [148]…”
Section: Protein-proteinmentioning
confidence: 99%
“…They confirmed that cholesterol significantly stabilized the antiparallel helix dimer interpreted as hydrophobic interaction. In another study two years later, they replaced the center of (AALALAA) 3 with the guest GXXXG motif [ 133 ]. Interestingly, transient dimerizations in both parallel and antiparallel topologies achieved an equilibrium, whereas the addition of cholesterol completely abolished the Gly-mediated associations.…”
Section: Tracking the Interactions Between Biomoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, continuous measurements of immobilised, confined, or encapsulated molecules permit transitions between conformational states to be measured [49,50] (typically in exchange for time resolution). Continuous smFRET measurements have been used with great effect to probe functional dynamics [51,52,53,54] and association dynamics [55,56,57,58] of membrane proteins in lipid bilayers. However, their application to membrane protein folding in a lipid bilayer environment is, to our knowledge, yet to be demonstrated; such a study was recently proposed by Krainer et al [59] and here we seek to address that call.…”
Section: Introductionmentioning
confidence: 99%